Respiratory symptoms in older people and use of domestic gas appliances. Issue 12 (1st December 1999) - Dow, L; Phelps, L; Fowler, L; Waters, K; Coggon, D; Holgate, S T
Abstract : BACKGROUND: Studies in children and young women have indicated an increased risk of respiratory illness in association with the use of domestic gas appliances, possibly caused by oxides of nitrogen generated when gas is burned. It is not known whether risks are similarly increased in older subjects. METHODS: A questionnaire about respiratory symptoms in the past year and potential risk factors for respiratory disease was mailed to 6000 men and women aged 65 years and older who were selected at random from the lists of general practices in North Bristol, UK. Associations between symptoms and the use of gas appliances were examined by logistic regression with adjustment for age, sex, social class, and smoking habits. RESULTS: Questionnaires were completed by 4792 (80%) of those mailed. The most common symptoms were exercise induced breathlessness, wheeze, or chest tightness (51%); wheeze (27%); morning phlegm (20%); and daytime breathlessness at rest (19%). In an analysis that included all subjects only weak associations were found with use of gas appliances, odds ratios all being 1.2 or less. The risks associated with use of a gas hob tended to be higher in women, with odds ratios of 1.36 (95% CI 1.01 to 1.83) for wheeze and 1.33 (95% CI 0.56 to 3.17) for morning chest tightness, but were lower than had been reported previously in younger women. CONCLUSION: The absence of stronger associations cannot readily be explained by bias or confounding. Gas cookers and fires are unlikely to be an important cause of respiratory illness in the elderly. If they do cause such illness, the largest risks are likely to be in women who use gas hobs.